“Science isn’t just what we learn in school”: Using video and arts-based methods to engage youth in science conversations - Gonsalves, Allison Jardim (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
In this article, I explore what happens when digital media activities designed to stimulate science conversations are introduced to an out-of-school-time (OST) space usually reserved for talks about girls’ issues. The goals of this study were to provide a space that values youth voice and creates positive emotional energy around science-related subjects. In this article, I identify episodes of interaction rituals that provoke positive emotional energy toward science among a group of adolescent girls in a community centre in a low-income urban neighbourhood. Results highlight moments when youth mobilize their funds of knowledge and demonstrate emotionally positive charged engagement with science. I then conclude with an exploration of the limitations of shifting ideas about what counts as “real science” and the implications for science teaching both in and out of the classroom. Résumé Cet article explore ce qui s’est passé lorsque des activités médiatiques digitales, destinées à stimuler les conversations à propos des sciences, ont été intégrées à un programme parascolaire habituellement réservé aux conversations entre adolescentes. Les objectifs de cette étude étaient de fournir un espace valorisant les voix des jeunes et créant une charge affective positive envers les sujets scientifiques. Cet article identifie les épisodes d’interaction ayant provoqué une charge affective positive envers les sciences chez un groupe d’adolescentes, dans un centre communautaire situé dans un quartier urbain défavorisé. Nous identifions les moments d’engagement positif avec la science grâce à la mobilisation de «fonds de connaissance» et par leurs «répertoires de pratique». Cependant, nous identifions également les limites des tentatives de changer ce qui est perçu comme «la vraie science» ou comment les jeunes se considèrent en relation avec la science, tant dans la classe qu’à l’extérieur de celle-ci.